Implementation of the Precautionary Principle in Banking: Implications for Customer Risk Financial - Andini, Pretty Fabiola; Wantu, Fence M. (Damhil Law Journal, 2023)
The purpose of the research is to find out more about the application of the Prudential Principle according to Article 2 and Article 29 of Law Number 10 of 1998 concerning Banking. This research uses normative research methods. The approach taken is to use a statutory approach, doctrinal approach, and comparative approach. The results of this study indicate that the prudential banking principles are essential in the world of banking in Indonesia, so they must be implemented or run by banks in carrying out their business activities. The current prudential banking regulation is contained in Law Number 10 of 1998. In addition, there are also circulars and decrees of the Board of Directors of Bank Indonesia. By using the Branchless Banking model in the banking industry, banks are required to implement prudential principles comprehensively. They must also provide security and protection to customers when using products in branchless banking.